Increased prevalence of carbapenem resistant Enterobacteriaceae in hospital setting due to cross-species transmission of the blaNDM-1 element and clonal spread of progenitor resistant strains - Wang, Xuan; Chen, Gongxiang; Wu, Xiaoyan; Wang, Liangping; Cai, Jiachang; Chan, Edward W.; Chen, Sheng; Zhang, Rong (Frontiers in Microbiology, 2015)
This study investigated the transmission characteristics of carbapenem-resistant Enterobacteriaceae (CRE) strains collected from a hospital setting in China, in which consistent emergence of CRE strains were observable during the period of May 2013 to February 2014. Among the 45 CRE isolates tested, 21 (47%) strains were found to harbor the blaNDM-1 element, and the rest of 24 CRE strains were all positive for blaKPC-2. The 21 blaNDM-1—borne strains were found to comprise multiple Enterobacteriaceae species including nine Enterobacter cloacae, three Escherichia coli, three Citrobacter freundii, two Klebsiella pneumoniae, two Klebsiella oxytoca, and two Morganella morganii strains, indicating that cross-species transmission of blaNDM-1 is a common event. Genetic analyses by PFGE and MLST showed that, with the exception of E. coli and E. cloacae, strains belonging to the same species were often genetically unrelated. In addition to blaNDM-1, several CRE strains were also found to harbor the blaKPC-2, blaVIM-1, and blaIMP-4 elements. Conjugations experiments confirmed that the majority of carbapenem resistance determinants were transferable. Taken together, our findings suggest that transmission of mobile resistance elements among members of Enterobacteriaceae and clonal spread of CRE strains may contribute synergistically to a rapid increase in the population of CRE in clinical settings, prompting a need to implement more rigorous infection control measures to arrest such vicious transmission cycle in CRE-prevalent areas.